Fundamentals of MALDI-ToF-MS analysis : applications in bio-diagnosis, tissue engineering and drug delivery /: applications in bio-diagnosis, tissue engineering and drug delivery. ([2016]) - Hosseini, Samira; Martínez Chapa, Sergio Omar
No abstract available